2020
DOI: 10.48198/njpas/20.a03
|View full text |Cite
|
Sign up to set email alerts
|

Study of antibiotics resistance in bacteria isolated from retailed eggshell in three major markets in Minna, Nigeria

Abstract: Food borne disease associated with inappropriately treated or untreated eggs is a major public health problem affecting developing and developed countries. This study isolated, identified and determined the Antibiogram of bacteria isolates from eggshell of eggs obtained from three major markets in Minna, Nigeria. A total of ten (10) duplicate egg samples were purchased from egg retailers. The egg samples were analyzed for the enumeration and isolation of bacteria. The isolated bacteria were identified using bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Several studies on different parts of the world, including Bangladesh (Haque et al, 2021), India (Arathy et al, 2009), Egypt (Mansour et al, 2015), Nigeria (Adabara et al, 2020), and South Africa (Jambalang et al, 2017) have revealed the presence of E. coli in table eggs. The same prevalence of E. coli in egg shells found in this study was previously reported in farm eggs in Nigeria (9.1%, Adabara et al, 2020). Regarding the egg shells, the prevalence of E. coli was detected in Zambia (Kapena et al, 2020), and Thailand (Siriporn et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies on different parts of the world, including Bangladesh (Haque et al, 2021), India (Arathy et al, 2009), Egypt (Mansour et al, 2015), Nigeria (Adabara et al, 2020), and South Africa (Jambalang et al, 2017) have revealed the presence of E. coli in table eggs. The same prevalence of E. coli in egg shells found in this study was previously reported in farm eggs in Nigeria (9.1%, Adabara et al, 2020). Regarding the egg shells, the prevalence of E. coli was detected in Zambia (Kapena et al, 2020), and Thailand (Siriporn et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the egg shells, the prevalence of E. coli was detected in Zambia (Kapena et al, 2020), and Thailand (Siriporn et al, 2015). Besides, E. coli was isolated from egg contents in several previous studies conducted in Trinidad, Egypt, and Nigeria (Adesiyun et al, 2005;Mansour et al, 2015;Adabara et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Nigerian eggs analysis from supermarkets (formal sector) has revealed the presence of E. coli , Salmonella spp., and Staphylococcus aureus ; in contrast to our study, Shigella spp. was also detected [ 14 ]. Moreover, Pseudomonas aeruginosa and Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%